Fatigue life study of suspension ball joints on the basis of ride quality - Kathri, Naveed (Inderscience Enterprises Ltd, 2020)
The MacPherson quarter car model was used to determine fatigue life of a suspension ball joint using a non-conventional approach which combined rigid body dynamics with finite element (FE) analysis. In this research, a quarter car model was subjected to International Standards Organization (ISO) random road profile with a pothole and a speed bump in order to obtain the ride quality and the reaction forces occurring at the ball joint. After classifying three ride qualities, another simulation was conducted on this model to study the stress distributions, in which the ball joint and its socket were treated as flexible bodies. Finally, based on the results of the FE analysis, fatigue life of the joint was measured for each ride quality. Based on the findings, it was concluded that a good ride quality has an adverse effect on the fatigue life of the ball joint component. ANSYS Workbench and CATIA V5 were used for modelling and simulation.